THE IMPORTANCE OF THE INNOVATION ECOSYSTEM FOR THE TRANSFORMATION OF REGIONAL ENTREPRENEURSHIP - THE ORGANA BIOTECH CASE STUDY - Novais da Silva, Fernando; Ottoni Zimmermann, Guilherme; Geiza, Andreia (Revista Gênero e Interdisciplinaridade, 2025)
This article presents a case study that emerged from within the innovation ecosystem of Joinville (SC), this ecosystem evolves every year in relation to the maturity index. The main objective is to show the nuances, stages, innovation events, involvement of the ecosystem entities, and highlight the results using a Startup that grows with the ecosystem, participating in the stages and doing its work in an integrated and orderly manner, with its own capital and increasingly appropriating its excellent service and becoming a reference in its area of ​​activity, the startup is Organa Biotech.This article shows the importance of having several open innovation initiatives involving industry, government and academia, to generate awareness and a culture of entrepreneurship, positioning the city as a city of innovation and entrepreneurship. When this is done in an orderly manner and with the involvement of all elements, it really works to generate results for the elements, generating results via the ecosystem with an impact on the city as a whole. The presentation of the Organa case is an example of an initiative coming from the ecosystem.